Respuesta :

For this case we have the following xpresion:

[tex]2y ^ 2 + 3y + 4y + 6[/tex]

We can rewrite it as:

[tex]2y ^ 2 + 7y + 6[/tex]

Where:

[tex]a = 2\\b = 7\\c = 6\\[/tex]

We must factor, for this we follow the steps below:

Step 1:

The term of the medium must be rewritten as the sum of two terms, whose sum is 7 and the product is [tex]a.c = 2 * (6) = 12[/tex]:

Then, the term of the medium, fulfilling the two previous conditions, can be written as:

[tex]4y + 3y[/tex]

We check:

[tex]4 * 3 = 12\\4 + 3 = 7[/tex]

So, we have:

[tex]2y ^ 2 + 4y + 3y + 6[/tex]

Step 2:

The maximum common denominator (the largest integer that divides them without leaving residue) of each group is factored

[tex]2y ^ 2 + 4y + 3y + 6\\2y (y + 2) + 3 * (y + 2)[/tex]

Step 3:

We take common factor [tex](y + 2)[/tex]:

[tex](y + 2) (2y + 3)[/tex]

Thus, the expression [tex]2y ^ 2 + 3y + 4y + 6[/tex] can be factored as:

[tex](y + 2) (2y + 3)[/tex]

Answer:

[tex](y + 2) (2y + 3)[/tex]